A Child and the Art in the First and the Second Grade of the Primary School - Kuščević, Dubravka; Brajčić, Marija; Matijašević, Ivana (Revija za elementarno izobraževanje, 2009)
The nature of the relation between the art and art teaching is dialectical. Art teaching is unthinkable and unrealizable without art substances, and a work of art can't achieve its full sense without educated person capable of experience. Starting from that fact came the idea to explore the perception of the art works at the children in the early school age, in this case at the children in the first and the second grade of the primary school, their preferences and the attitude towards the works of art. It was tried to figure out how much children of the lower school age like to view the works of art and the preferences of the pupils of the lower school age (first and second grades of primary schools) according to work of arts of traditional or modern artistic expression (controlling the influence of the variable — gender), drawings or paintings, figurative or abstract presentation. Children of early school age in a higher percentage choose paintings in relation to drawings (81 % of the pupils of the first grade and 79% of the second grade). Most of the children of the lower school age (69% of the pupils of the first grade and 76% of the second grade) prefer figurative in relation to abstract expression. Most of the children of the lower school age like to view art work.